The influence of nuclear compartmentalisation on stochastic dynamics of self-repressing gene expression. (7th July 2017) - Sturrock, Marc; Li, Shiyu; Shahrezaei, Vahid
Highlights: Negative feedback decreases protein noise but can increase mRNA noise. Nuclear compartmentalisation decreases mRNA noise but can increase protein noise. Negative feedback or nuclear compartmentalisation can be more effective in reducing protein noise depending on nuclear translocation rates. Nuclear compartmentalisation and negative feedback can increase or decrease noise levels depending on nuclear translocation rates. Nuclear compartmentalisation can increase regularity of protein spiking for a self-repressing gene. Abstract: Gene expression is an inherently noisy process. This noise is generally thought to be deleterious as precise internal regulation of biochemical reactions is essential for cell growth and survival. Self-repression of gene expression, which is the simplest form of a negative feedback loop, is commonly believed to be employed by cellular systems to decrease the stochastic fluctuations in gene expression. When there is some delay in autoregulation, it is also believed that this system can generate oscillations. In eukaryotic cells, mRNAs that are synthesised in the nucleus must be exported to the cytoplasm to function in protein synthesis, whereas proteins must be transported into the nucleus from the cytoplasm to regulate the expression levels of genes. Nuclear transport thus plays a critical role in eukaryotic gene expression and regulation. Some recent studies have suggested that nuclear retention of mRNAs can control noise in mRNA expression. However, the effect of nuclear transport on protein noise and its interplay with negative feedback regulation is not completely understood. In this paper, we systematically compare four different simple models of gene expression. By using simulations and applying the linear noise approximation to the corresponding chemical master equations, we investigate the influence of nuclear import and export on noise in gene expression in a negative autoregulatory feedback loop. We first present results consistent with the literature, i.e., that negative feedback can effectively buffer the variability in protein levels, and nuclear retention can decrease mRNA noise levels. Interestingly we find that when negative feedback is combined with nuclear retention, an amplification in gene expression noise can be observed and is dependant on nuclear translocation rates. Finally, we investigate the effect of nuclear compartmentalisation on the ability of self-repressing genes to exhibit stochastic oscillatory dynamics.